2014 IEEE International Conference on Data Mining 2014
DOI: 10.1109/icdm.2014.112
|View full text |Cite
|
Sign up to set email alerts
|

LorSLIM: Low Rank Sparse Linear Methods for Top-N Recommendations

Abstract: In this paper, we notice that sparse and low-rank structures arise in the context of many collaborative filtering applications where the underlying graphs have block-diagonal adjacency matrices. Therefore, we propose a novel Sparse and Low-Rank Linear Method (LorSLIM) to capture such structures and apply this model to improve the accuracy of the Top-N recommendation. Precisely, a sparse and low-rank aggregation coefficient matrix W is learned from LorSLIM by solving an 1-norm and nuclear norm regularized optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 19 publications
0
24
0
Order By: Relevance
“…In general, a recommender system models the user preference though the user profiles, such as the user-item pair. The MF is a successful method to model the user preferences with two latent-factors by factorizing the user-item matrix [40][41][42]. A user preference for the item i that presents ̂ is represented by the user-item latent factors ( and ).…”
Section: B Modeling User Preferencementioning
confidence: 99%
“…In general, a recommender system models the user preference though the user profiles, such as the user-item pair. The MF is a successful method to model the user preferences with two latent-factors by factorizing the user-item matrix [40][41][42]. A user preference for the item i that presents ̂ is represented by the user-item latent factors ( and ).…”
Section: B Modeling User Preferencementioning
confidence: 99%
“…The optimization problem 4 is usually dealt in several works [19,20,5,30] in field of Top-N recommendation problem. Recently, [30] showed that this problem could be simply solved in closed form by method of Lagrange multipliers.…”
Section: Closed Form Solution Of Self-expressive Layermentioning
confidence: 99%
“…It has been shown that SLIM outperforms other Top-N recommendation methods. A drawback of SLIM is that it can only model relations between items that have been co-purchased/co-rated by at least one user [13]. Therefore, it fails to capture the potential dependencies between items that have not been co-rated by at least one user, while modeling relations between items that are not co-rated is essential for good performance of item-based approaches in sparse datasets.…”
Section: Relevant Researchmentioning
confidence: 99%
“…We compare the performance of the proposed method with seven stateof-the-art Top-N recommendation algorithms, including the item neighborhood-based collaborative filtering method ItemKNN [9], two MF-based methods PureSVD [11] and WRMF [34], SLIM [8] and LorSLIM [13]. We also examine two ranking/retrieval criteria based methods BPRMF and BPRKNN [35], where Bayesian personalized ranking (BPR) criterion is used which measures the difference between the rankings of userpurchased items and the remaining items.…”
Section: Comparison Algorithmsmentioning
confidence: 99%